Factors Influencing Intention to Use Cloud Storage Services Amongst Postgraduate - Bazel, Mahmood A.; Hasnah, Haron; Ishak, Ismail; Suryanto; Gui, Anderes (IEEE, 2018)
The purpose of this research is to supply empirical evidence about the acceptance of Cloud Storage Services (CSS), by attempting to build an enhanced research framework with based on the Technology Acceptance Model (TAM) to identify factors that affect postgraduate students' intentions to use CSS. Factors examined are cloud storage service support, cloud storage self- efficacy, perceived usefulness and perceived ease of use on intention to use CSS. Using convenience sampling method, a total of 219 postgraduate students from 4 Malaysian technical universities participated in the study. Structured equation modelling was used to analyse the data and findings indicate that CSS support have a significant positive relationship with ‘‘perceived usefulness’’, and ‘‘cloud storage self-efficacy’’ have significant positive relationship on the ‘‘perceived ease of use”. Both “perceived usefulness” and “perceived ease of use” have a significant relationship on students’ intention to use CSS. The findings of this study can help the service providers to develop successful strategic plans for usage of CSS. Universities should also have policy and guidelines in using services to ensure the security when access information from intranet.